Etiology and Outcome of Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The prognostic value of seizure etiology, neurologic examination, EEG, and neuroimaging in the neurodevelopmental outcome of 89 term infants with neonatal seizures was determined at the Children's Hospital and Harvard Medical School, Boston, MA.